MODEL PERHITUNGAN PENDAPATAN NASIONAL DALAM PERSPEKTIF EKONOMI ISLAM - Dumairy, Syamsul Hadi, Muhammad (Arabic Literature Department, 2018)
In conventional economics one will find a basic macroeconomic model formulated as Y=C+I+G. This basic model is a formulae for counting national income with expenditure approach. Economists and economic students are quite familiar with it. According to conventional economists, in any economy there are three sectors that spend expenditures and earn income; those are household, business, and the government sectors. Economic actors or agents in household sector are individuals or families. Actors in business sector consist of firms, companies, or corporations. The actor in the government sector is the central government as an institutional entity. In the aforementioned model C symbolizes expenditures spent by household sector, I reflects investment spending by business sector, while G represents the government expenditure. This article is the product of a research which reveals that the basic macroeconomic model Y=C+I+G is less realistic. National income figures resulted from applying that model have been underestimated. Not only the model less realistic, underlying assumptions in building the model also are not Islamic. It is even worse that those assumptions have also been proven unfitted to the real world.Endowed with concepts in Islamic economics, this article provides a new model, a model that is not merely Islamic but more realistic as well. In the model being proposed here an additional economic sector is introduced, namely, social sector. Economic actors or agents in this sector consist of social organizations and non-profit institutions, a segment of community whose role and economic contributions have so far been neglected in conventional economics. Now in our presently proposed model, by recognizing them as a specific economic entity the new basic macroeconomic model is to be Y=”C”+”I”+G+A.